Metadata privacy and obliviousness in distributed learning via a bulletin board: a proof-of-concept - Purim, Andreis G. M.; Oliveira, Witor M. A.; Souza, Allan M. de (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2026)
While many works study payload privacy in distributed learning, metadata and communication patterns between peers can still reveal sensitive information. We treat metadata privacy as a distinct problem, and first introduces a risk and threat model for metadata leakage in distributed learning systems. Building on this analysis, we present a bulletin board-based communication architecture in which peers exchange activations, gradients, and model updates under configurable privacy and efficiency settings. We implement a proof-of-concept code of the proposed design and evaluate it on small-scale distributed learning workloads, which is available on Github.